In Vitro Evaluation of Cholesterol-Reducing Ability of Chitosan from Mangrove Crab (Scylla serrata) Shell Solid Dispersion using PVP K-30 as a Carrier: Uji In Vitro Penurunan Kadar Kolesterol Sistem Dispersi Padat Kitosan dari Cangkang Kepiting Bakau (Scylla serrata) Menggunakan PVP K-30 Sebagai Pembawa - Imtihani, Hilya Nur; Permatasari, Silfiana Nisa; Prasetya, Rahmad Aji (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Background: Chitosan is a compound that can be synthesized from nature which can reduce the total serum cholesterol levels between 5.8âˆ’42.6% and decrease LDL (Low-Density Lipoprotein) between 15.1-35.1%. One of the natural resources containing chitosan derivative compounds is the shell of mud crab. Chitosan is insoluble in water but soluble in acidic solutions such as acetic acid. With such chitosan solubility, it is necessary to increase the solubility by making a solid dispersion system so that drug absorption can be faster. Objectives: The aims of this study is to determine the potential of chitosan solid dispersion system for reducing cholesterol. Material and Methods: The reduction of cholesterol levels was carried out by in vitro tests using UV-Vis spectrophotometer at a wavelength of 405 nm with Lieberman-Burchad reagent. The positive control used was simvastatin. There are 4 formulas, namely SD1, PM1, SD2, and PM2. This solid dispersion system uses polyvinyl pyrrolidone K-30 (PVP K-30) as carrier. Results: The characterization of chitosan has fulfilled all the characterization requirements that is organoleptic (shape and color) was creamy white, moisture content was 2.15%, ash content was 1.14%, ninhydrin test was positive purple, and deacetylation degree was 70.57%. The results of in vitro evaluation were obtained a dark green solution. The reducing percentage in cholesterol levels are SD1: 18.44%; PM1 : 18.11%; SD2 : 29.57%; and PM2 :12.01%. Simvastatin as a positive control has a percentage reduction in cholesterol levels of 30.07%. Conclusion: Chitosan has an activity as anticholesterol agent. SD2 (Solid Dispersion Chitosan: PVP K-30 = 1:2) has the higher percentage than other formulas for reducing cholesterol level comparable with the positive control.